Narrative Closure in the Post-Apocalyptic Novels of Cormac McCarthy and Colson Whitehead: A Comparative Perspective (مجلة ديالى للبحوث الانسانية, 2025)
This study explores the phenomenon of narrative closure in the post-apocalyptic novels of Cormac McCarthy and Colson Whitehead, namely The Road and Zone One. However, this study does not seek to find out whether there is narrative closure in the post-apocalyptic novels of these two novelists. It instead seeks to uncover the exact textual mechanisms that operate in such narratives to fashion or deny closure at the level of plot structure and show how these novelists subvert narrative closure to destabilize the re-invention of humanity to mount a critique on the liberal ideologies that shape the intellectual horizons of the early twenty-first century America that produced them.